PROPOSE NEW DIGITAL PRODUCT DEVELOPMENT FOR SME CUSTOMER IN BANK ARTMS - Rahmat Putra, hafisyah
The SME sector in Indonesia, which comprised 62 million businesses, played a pivotal role as a catalyst for economic growth and employment, particularly evident during crises such as the COVID-19 pandemic. In this context, banking institutions like Bank ARTMS offered services such as loans and other activities that directly supported and strengthened SME businesses. As part of its strategic initiatives, Bank ARTMS aimed to create a digital bank facilitating swift and contactless financial transactions for SME customers called ARTMS Bisnis. However, the historical perception of the bank primarily as a loan provider, rather than a transactional bank, hindered the product's traction. At that time, ARTMS Bisnis had garnered only 1,700 customers, with less than 50% actively participating in transactions. This limited traction was also attributed to a lack of features compared to competitors, highlighting the need for enhanced functionality to attract and engage customers effectively. In that study, the author conducted interviews with various respondents, including existing customers, non-customers, internal employees, and experts. The aim was to gain insights into enhancing the digital experience of SME customers through a digital bank. The author employed strategic tools such as Pestel analysis, competitor analysis, STP analysis, persona analysis, root cause analysis, and SWOT analysis to formulate an effective strategy. This comprehensive approach aimed to develop a unique and valuable product tailored to the specific needs and preferences of SME customers. After conducting the research, gain creator and pain reliever develop by using the value proposition canvas. These result shows the need of a comprehensive digital bank feature development that offered end-to-end integration, digital assistance, gamification, award incentives, business reporting tools, digital loan applications, and the introduction of derivative digital products that supported multiple facets of SME customer businesses, including Payroll, Request Payment, Bills, and QRIS transactions.